Hybrid Projection Algorithm for Two Countable Families of Hemirelatively Nonexpansive Mappings and Applications - Zi-Ming Wang; Poom Kumam (Journal of Applied Mathematics)
Two countable families of hemirelatively nonexpansive mappings are considered based on a hybrid projection algorithm. Strong convergence theorems of iterative sequences are obtained in an uniformly convex and uniformly smooth Banach space. As applications, convex feasibility problems, equilibrium problems, variational inequality problems, and zeros of maximal monotone operators are studied.